2022
DOI: 10.3390/ijerph19095415
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Bruxism, Stress, and Manifestations of Temporomandibular Disorder in Young Students

Abstract: Bruxism is a repetitive activity of the masticatory muscles, which determine teeth grinding or clenching, associated with rigidity, bracing, or thrusting of the mandibula. The aim of this study was to determine the prevalence of possible bruxism in 328 students attending the Faculty of Dental Medicine, University of Medicine and Pharmacy of Craiova, and its associations with stress and other manifestations of the temporo-mandibular disorder. This was a questionnaire-based study to collect information on self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
0
9
0
2
Order By: Relevance
“…As far as other sleep characteristics, Vladutu et al demonstrated that, among 328 university students, the prevalence of sleep bruxism was 16.28%, and it was significantly associated with COVID-related stress, while Winocur-Arias et al found that sleep bruxism was more prevalent exclusively in women during the pandemic [ 72 , 73 ]. In addition to that, oneiric activity was also modified during the pandemic.…”
Section: Sleep Disorders In General Population During Covid-19 Pandemicmentioning
confidence: 99%
“…As far as other sleep characteristics, Vladutu et al demonstrated that, among 328 university students, the prevalence of sleep bruxism was 16.28%, and it was significantly associated with COVID-related stress, while Winocur-Arias et al found that sleep bruxism was more prevalent exclusively in women during the pandemic [ 72 , 73 ]. In addition to that, oneiric activity was also modified during the pandemic.…”
Section: Sleep Disorders In General Population During Covid-19 Pandemicmentioning
confidence: 99%
“…Uma pesquisa desenvolvida por Vlăduțu et al (2022) com crianças de ensino fundamental, cujo intuito era verificar o nível de ansiedade relacionado à presença ou não de DTM explicitou, através da aplicação do questionário de Heikimo, que crianças com a patologia apresentam altos níveis de ansiedade em oposição a níveis médios relacionados às outras crianças.…”
Section: Resultsunclassified
“…The T-Scan III system developed by Tekscan (Boston, MA, USA) uses the computer to analyze the occlusion in dynamics, allowing both qualitative and quantitative occlusal analyses to be performed simultaneously and with high precision. In fact, during the past years, scientists have actively involved technology through software applications or medical devices to increase the accuracy of the diagnostic process in dentistry and in medicine in general [ 24 , 25 , 26 ]. The T-Scan system can measure the sequence of dental contacts and quantitative dynamics in relation to time, locate excessive occlusal forces, and record the time from the first contact to the end of the movement [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present research was carried out during the years 2021–2022 within the Faculty of Dental Medicine Craiova on a number of 328 students, aged between 21 and 41 years, of both genders [ 24 , 37 ]. Inclusion in the study was performed on a voluntary basis, and the diagnosis of “possible” and “certain” bruxism was made according to the recommendations of the Consensus on bruxism [ 5 ] and the recommendations of STAB [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation